Global monitoring report 2013 rural-urban dynamics and the millennium development goals. (World Bank, 2013)
The report provides information about the differences in progress toward the MDGs across geographical areas and recognizes that urban populations are better off than their rural brethren. However, unfettered urbanization can cause migrants and the urban poor to end up in slums where attainment of the MDGs lags. GMR 2013 calls for an integrated strategy to better manage the planning-connecting-financing formula of urbanization. Notwithstanding the importance of urbanization in poverty reduction and MDG attainment, rural areas remain a huge challenge?one that underscores the importance of policies that can improve rural livelihoods. The rural-urban spectrum ranges from small towns to large cities. The general experience is that poverty is lowest in the largest cities and considerably higher in smaller towns.